2024
DOI: 10.1039/d3ee04556k
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a multi-system adaptable gel polymer electrolyte for the realization of carbonate ester and ether-based Li-SPAN batteries

Yan Zhang,
Zhaokun Wang,
Yanrui Pan
et al.

Abstract: Sulfurized polyacrylonitrile (SPAN) is deemed as a prospective replacement cathode in high-energy-density lithium-sulfur batteries. Conventional carbonate electrolytes, most widely employed in Li-SPAN batteries, exhibit chemical in-compatibility with lithium (Li) metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In comparison to catholyte-type dissolution–deposition and/or complete S 8 -Na 2 S x (1 ≤ x ≤ 3) solid-to-solid sulfur redox chemistry, the unique quasi-solid sulfur conversion can achieve a good balance between efficient sulfur reutilization and fast redox kinetics especially within a solid system. 1,10,12,16,17 However, studies on understanding the sulfur redox in low-temperature (<100 °C) batteries using solid electrolytes are still in their infancy. 13,18–20 Seminal works showed that the soft PEO-NaFSI gel binder could efficiently overcome the interfacial challenges and facilitate a continuous 3D ionic transport path in solid-state metal–sulfur batteries, thus providing a deeper understanding of the redox chemistry during dynamic battery discharge/charge.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to catholyte-type dissolution–deposition and/or complete S 8 -Na 2 S x (1 ≤ x ≤ 3) solid-to-solid sulfur redox chemistry, the unique quasi-solid sulfur conversion can achieve a good balance between efficient sulfur reutilization and fast redox kinetics especially within a solid system. 1,10,12,16,17 However, studies on understanding the sulfur redox in low-temperature (<100 °C) batteries using solid electrolytes are still in their infancy. 13,18–20 Seminal works showed that the soft PEO-NaFSI gel binder could efficiently overcome the interfacial challenges and facilitate a continuous 3D ionic transport path in solid-state metal–sulfur batteries, thus providing a deeper understanding of the redox chemistry during dynamic battery discharge/charge.…”
Section: Introductionmentioning
confidence: 99%